Temporary works : principles of design and construction. - Pallett, Peter F.; Filip, Ray (ICE Publishing, 2018)
With contributions from over thirty industry experts, this reference book covers all sub-specialities of temporary works within a single volume. Informed by the latest UK Regulations and use of European codes in the UK, chapters consider the how and why of current methods across a wide range of topics. Drawing on years of collective experience of temporary works in practice the book is a source of immediate, practical solutions to common problems and also includes an extensive list of references for each subject. This new edition brings up to date the topics inherent in temporary works in the original 27 chapters and includes seven new chapters on backpropping, basement construction, needling, pipe testing, rebar stability, digital project delivery, and temporary works in demolition.
Previous edition: 2012.
Keywords: Temporary structures (Building); elektronické knihy; electronic books